Geomorphological maps of anthropogenic landscapes: methodology, conceptual bases, contents and legend structure - Rodrigues, Cleide (2024)
The role of geomorphological mapping as a tool for assessing the extent of physical anthropogenic changes in historical intervals has been developed by urbanization studies of São Paulo, carried out in the Department of Geography of University of São Paulo over the last three decades. This article sumarizes the consolidated procedures of this production, called anthropogenic geomorphological mapping and presents the basic conceptual repertoire consolidated and created, the organization of the structure of legends, the most relevant contents to be mapped in different conditions of landscapes, such as high preservated landscapes called ‘original morphology’, or landscapes with different degrees of anthropization, called 'anthropogenic morphology'. It demonstrates the importance in taking account the sequences of anthropogenic interventions and the identification of even more complex morphologies units, that can be revealed with the superpositions of original morphology and anthropogenic sequences, always considering the hydromorphological systems as a reference for subsequent evaluations. This article also presentes and discusses some graphic representations used in accordance with the various mapping scales, useful spatial correlations of mapped contents and their relationship with the consolidated procedures of detailed geomorphological cartography and offering a basic guide for the production of geomorphological cartography of anthropogenic landscapes.